Review Boichuk NV et al., authors; Ulumbekov EG, Chelyshev YuA, editors. Gistologiya. Embriologiya. Tsitologiya [Histology. Embryology. Cytology]: textbook. Ed. 4th, revised and additional. Moscow: GEOTAR-Media; 2016. 927 p. Russian. - journal "Morphologia", Editorial office of (Морфологія / Morphologia / Morfologìâ, 2017)
The fourth edition of the textbook has been revised and updated in accordance with the curricula of medical schools on histology, embryology and cytology.